Negotiating with frictions - Volker Britz (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
We consider bilateral non-cooperative bargaining on the division of a surplus. Compared to the canonical bargaining game in the tradition of Rubinstein, we introduce additional sources of friction into the bargaining process: Implementation of an agreement and consumption of the surplus can only begin at discrete points in time, such as the first day of a month, quarter, or year. Bargaining rounds are of non-trivial length, so that counter-offers may be made without triggering costly delay. Communication between players is noisy: When players make offers, they are uncertain about the time it takes for the offer to arrive. We analyze delays and payoffs in the unique stationary equilibrium of the game. Frictions tend to make the bargaining process less efficient, but lead to a fairer surplus allocation. We establish conditions under which the equilibrium outcome converges to that in a canonical bargaining model as frictions become small.
Keywords: C72; C78; 330; Bargaining; Discount Factor; Timing; Subgame-Perfect Equilibrium; Equilibrium Delay